Reorganization of the cytoskeleton - Vincze, Gyula; Szigeti, Gyula Peter (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The effect of a modulated electromagnetic field on the cytoskeleton is possible through the action of voltage-sensitive phosphatase (VSP). Field-controlled phosphorous hydrolysis could have important roles in cytoskeleton restructuring, as well as in resonant-type behavior.